The Development Of Interactive Media Using Scratch To Improve Social Science Learning Outcomes Of Fifth Grade Students At Sdn 101776 Sampali In The 2024/2025 Academic Year - Pane, Aina Ristanti; Yus, Anita; Lubis, Wildansyah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to develop interactive media using the Scratch web application that is valid, practical, and effective in improving the learning outcomes in IPAS for fifth-grade students at SD Negeri 101776 Sampali in the 2024/2025 academic year. This type of research is Research and Development (RD) using the 4D development model, which consists of four stages: (1) Define; (2) Design; (3) Development; and (4) Disseminate. The findings of this study are: (1) The feasibility of the media was determined based on validation results from subject matter, media, and language experts. The subject matter expert validation obtained a final score of 93.3% with a “Highly Feasible” criterion. Media expert validation was conducted in two stages: the first stage yielded a score of 83% (“Feasible” with revisions), and the second stage reached 90.6% (“Highly Feasible”). Language expert validation scored 89% (“Highly Feasible”). (2) The practicality of the media was measured through practicality questionnaires distributed to teachers and students. The teacher’s response showed a practicality score of 88% (“Highly Practical”), and the students’ response was 90% (“Highly Practical”). (3) The effectiveness of the media was evaluated by the gain test result was 0.71, categorized as “Very High,” indicating that the interactive media “Scratch” has a high level of effectiveness in improving learning outcomes. The conclution of this research is the developed Scratch interactive media is valid, practical, and effective for enhancing student learning outcomes in the IPAS subject for Grade V at SD Negeri 101776 Sampali